Establishing the Correlations for Eco-Efficiency Index of Various Types of Structural Concrete Used in the Malaysian Housing Using Response Surface Method - Mohd Samsudin Abdul Hamid; Nasir Shafiq; Osamah Kiwan (Applied Sciences, 2020)
The concept of a sustainable environment generally refers to the development that creates a balance between the resources consumption pattern and the rate of depletion of natural resources. For determining the level of sustainability of any project, three types of impacts are assessed: economic, environmental, and social. This paper presents an analytical study that focused on establishing a correlation of eco-efficiency index for low-rise reinforced concrete residential housing in Malaysia. A statistical technique using the response surface method was performed, with the help of design expert software. The data was verified using regression analysis and represented by R2 value, standard deviation, and coefficient of variation. By using economic factors, environmental factors, and the eco-efficiency index, 3D model graphs were developed for structural concrete containing fly ash, and blast furnace slag (BFS), which was assigned to the structural members in a single and double story housing. The study has concluded that the correlations established between the cost and carbon emission, economic & environmental scores, and the eco-efficiency index have shown a linear trend for single story housing and a cubic for the double story housing.